Researching the impact of electric boat hull aeration energy consumption - Łebkowski, A. (Scientific Journal of Gdynia Maritime University, 2017)
The paper presents the results of research on the hull aeration system for an electric powered boat. The examples of marine vessels with such technology is used for minimization of energy use and CO2 emissions are shown. The currently known methods for lowering the fuel consumption in watercraft are discussed.